Web Technologies and Applications 14th Asia-Pacific Web Conference, APWeb 2012, Kunming, China, April 11-13, 2012. Proceedings - Sheng, Quan Z.; Wang, Guoren; Jensen, Christian S.; Xu, Guandong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 14th Asia-Pacific Conference APWeb 2012 held in Kunming, China, in April 2012. The 39 full papers presented together with 34 short papers, 2 keynote talks, and 5 demo papers were carefully reviewed and selected from 167 initial submissions. The papers cover contemporary topics in the fields of Web management and World Wide Web related research and applications, such as advanced application of databases, cloud computing, content management, data mining and knowledge discovery, distributed and parallel processing, grid computing, internet of things, semantic Web and Web ontology, security, privacy and trust, sensor networks, service-oriented computing, Web community analysis, Web mining and social networks.
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Optical pattern recognition; Computer Science; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computer Communication Networks; Pattern Recognition; Database Management